Pengaruh Penerapan Corporate Social Responsibility terhadap Persepsi Nasabah Bank dan Dampaknya terhadap Corporate Image - Nasir, Muhadjir; Qurani, Gita Fitri (Journal the Winners: Economics, Business, Management, and Information System Journal, 2011)
The application of corporate social responsibility (CSR) in Indonesia is regulated in UU No. 40 2007 about company liability on article 74 which mentions the social responsibility to be borne by any corporations. CSR is one of the government's efforts to balance the economic growth and equitability. This study aims to determine how much CSR influences customer’s perceptions and its impact on corporate image of BNI. This study uses descriptive-associative method with unit analysis of customers of Bank BNI Fatmawati branch and survey analysis. Data collection uses questionnaires, interviews and literature study of previous researches. Data process uses SPSS 16.0 through validity and reliability, normality test, path analysis, and comparison of the average score through descriptive analysis. The study states that CSR brings effect to corporate image both directly and indirectly through the customer’s perception. Therefore, it is expected to continue to maintain BNI social sharing through their CSR programs and enhance public communication, so that the CSR transfer to change the customer’s perception leads to a positive success.